Optimal placement of FACTS devices in power transmission network using power stability index and fast voltage stability index - Roshan, Rakesh; Samal, Padarbinda; Sinha, Pampa (2020 International Conference on Electrical and Electronics Engineering (ICE3), 2020)
In this paper two techniques have been introduced to locate suitable position of FACTS devices in 14 bus IEEE interconnected transmission network to improve voltage profile, enhance power transfer capability and increase the efficiency of the overall power transmission. The techniques introduced here are power stability index (PSI) and fast voltage stability index (FVSI). These indices are calculated from the data obtained after performing load flow analysis in 14 bus IEEE interconnected transmission networks by using Newton Rapson's method in MIPOWER software. The FVSI technique shows better results in terms of reduction of reactive power losses, minimization of active and reactive power flow and The PSI technique shows better result in the reduction of active power losses.